In vitro tracking of phospholipase A(2) from snake venom conjugated with magic-sized quantum dots - Dias, Edigar H. V.; Pereira, Deborah F. C.; Sousa, Bruna B. de [UNESP]; Matias, Mariana S.; Queiroz, Mayara R. de; Santiago, Fernanda M.; Silva, Anielle C. A.; Dantas, Noelio O.; Santos-Filho, Norival Alves [UNESP]; Oliveira, Fabio de (Elsevier B.V., 2019)
Phospholipases A(2) represent a family of enzymes with important application in medicine. However, direct tracking is difficult due to the absence of a stable, effective and specific marker for these enzymes. Magic-sized quantum dots (MSQDs) are inorganic semiconducting nanocrystals with unique physical properties. They have the ability to conjugate to proteins, making them excellent markers for biological systems. In this work, we labelled phospholipase A(2) from Bothrops alternatus snake venom with Cadmium selenide (CdSe)/cadmium sulphate (CdS) MSQDs-a biocompatible and luminescent probe. Bioconjugation was confirmed using infrared spectra and fluorescence microscopy, which demonstrated that the CdSe/CdS MSQDs interact with phospholipase A(2) without interfering with its activity. This probe may be an important tool for the elucidation of many biological mechanisms, because it allows the pathway of phospholipase A(2) to be tracked from its entry through the plasma membrane until its incorporation into the nucleus of myoblasts. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Luminescent probe; Phospholipase A(2); Magic-sized quantum dot